2016
DOI: 10.1007/s13320-016-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the electromagnetic impulses from long-pulse laser illuminating solid targets inside a laser facility

Abstract: Emission of the electromagnetic pulses (EMP) due to laser-target interaction in laser facility had been evaluated using a cone antenna in this work. The microwave in frequencies ranging from several hundreds of MHz to 2 GHz was recorded when long-pulse lasers with several thousands of joules illuminated the solid targets, meanwhile the voltage signals from 1 V to 4 V were captured as functions of laser energy and backlight laser, where the corresponding electric field strengths were obtained by simulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The EMP amplitude was approximately proportional to r 1 2 / when electromagnetic waves propagated inside the target chamber (vacuum) [10], where r was the distance from the measuring location to the TCC. Compared to the electromagnetic wave proceeding inside the target chamber, there are many objects outside the target chamber such as laser facility diagnostic devices and concrete walls that can adsorb or scatter EMPs, so EMP outside the target chamber will degrade at a much faster rate [29], which can be verified by the multiple shielding layers of 0.5 mm PTFE, 0.4 mm copper film and 2.4 mm lead [30] that attenuate EMP amplitude over 448 times.…”
Section: Resultsmentioning
confidence: 99%
“…The EMP amplitude was approximately proportional to r 1 2 / when electromagnetic waves propagated inside the target chamber (vacuum) [10], where r was the distance from the measuring location to the TCC. Compared to the electromagnetic wave proceeding inside the target chamber, there are many objects outside the target chamber such as laser facility diagnostic devices and concrete walls that can adsorb or scatter EMPs, so EMP outside the target chamber will degrade at a much faster rate [29], which can be verified by the multiple shielding layers of 0.5 mm PTFE, 0.4 mm copper film and 2.4 mm lead [30] that attenuate EMP amplitude over 448 times.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of EMP generation in this facility by using nanosecond beams have been reported in Refs. [104][105][106]. An experiment carried out on SG-II-UP, with ps laser pulses with energy of a few hundred joules, is described here.…”
Section: Emp Experiments On Shen-guang III (Lfrc) Andmentioning
confidence: 99%
“…With the advent of the petawatt power and megajoule energy laser facilities a systematic effort was made to study the EMP phenomenon [2][3][4][5][6][7]. Despite these efforts a full quantitative understanding of this effect has not yet been attained and the problem continues to attract attention [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], with the interest driven by the fact that several multi-PW short-pulse laser facilities -such as the Extreme Light Infrastructure lasers in Prague, Szeged and Bucharestwould come online in near future.…”
Section: Introductionmentioning
confidence: 99%